Head rubbing and licking reinforce social bonds in a group of captive African lions, Panthera leo. - Tomoyuki Matoba; Nobuyuki Kutsukake; Toshikazu Hasegawa (PLoS ONE, 2013)
Many social animals have a species-specific repertoire of affiliative behaviours that characterise individualised relationships within a group. To date, however, quantitative studies on intragroup affiliative behaviours in social carnivores have been limited. Here, we investigated the social functions of the two most commonly observed affiliative behaviours in captive African lions (Panthera leo): head rubbing and licking. We conducted behavioural observations on a captive group of lions composed of 7 males and 14 females, and tested hypotheses regarding three social functions: tension reduction, social bonding, and social status expression. Disproportionately frequent male-male and female-to-male head rubbing was observed, while more than 95% of all licking interactions occurred in female-female dyads. In accordance with the social bond hypothesis, and in disagreement with the social status expression hypothesis, both head rubbing and licking interactions were reciprocal. After controlling for spatial association, the dyadic frequency of head rubbing was negatively correlated with age difference while licking was positively correlated with relatedness. Group reunion after daily separation did not affect the frequencies of the affiliative behaviours, which was in disagreement with the predictions from the tension reduction hypothesis. These results support the social bond hypothesis for the functions of head rubbing and licking. Different patterns of affiliative behaviour between the sexes may reflect differences in the relationship quality in each sex or the differential predisposition to licking due to its original function in offspring care.